MENINJAU BUKTI ILMIAH KEKUATAN BESI MENURUT CARA PANDANG ILMU KIMIA DAN SAINS YANG BERKAITAN BESERTA BEBERAPA KONSEKUENSINYA SEBAGAIMANA DISEBUT DALAM AL QURAN QS. AL HADIID:25 - Dede Suhendar (JURNAL ISTEK, 2011)
Kauniyah verses of iron in the Qur'an Surah Al Hadiid, Verse 25, in particular, has not been widely studied in the perspective of chemistry, let the problems associated with its implementation according to what is listed in the verse. In this paper, we discussed about of “great strength of iron” in the verse from the viewpoint of modern chemistry supported with findings of iron in other scientific disciplines are closely related with, as in Geology, Physics, Biology and Materials Science. In this paper, we also discussed the meaning of the next sentence of the verse "...and that Allah may know who is helping (religion) Him and His apostles but God has not seen." The discussion is limited to a review of the nuclear chemistry (nuclides), chemical structure, magnetic, and chemical bonding properties. We can be concluded that the iron does have remarkable properties leading to iron predicate as stated in the verse. The facts of iron are following: (1) Iron is an element with isotopes that have the most stable nucleus of all the existing elements; (2) Iron has metal structure (polymorph) that adaptive to the presence of other metal/s or elements in its structure, so it can be made many variations of steel/alloy; (3) Iron has the strongest magnetic effect on life on earth; and (4) The nature of the bonds formed between the iron with organic compounds of iron proved a major role in biochemical processes. Finally, the great strength of the iron phenomenon has consequences as a reflection of Muslims in order to use it in various forms that lead to the establishment of Islamic symbols.